Trapunto Quilting Innovation on Sasirangan Fabric and Community Response in South Kalimantan - Lusi Arianti; Nurul Hidayati (Gondang: Jurnal Seni dan Budaya, 2025)
The Akara Jukun Sasirangan fashion collection is inspired by the unique destination of Pasar Terapung. “Akara” comes from the Sanskrit language meaning form, while ‘Jukun Sasirangan’ comes from the Banjar language, meaning boat and Sasirangan fabric. This concept depicts the activities of people who conduct buying and selling transactions on a boat floating on the river. This urban style fashion design was developed based on Sasirangan fabric by applying trapunto quilting technique, adjusted to the character of modern, dynamic, and functional urban style. The design process began with an exploration of the latest fashion trends to determine silhouettes and design details that suit the tastes of women aged 17-35 years in South Kalimantan. This research uses a qualitative descriptive method that includes the stages of exploration, design, realization, and data collection of community responses. The results of the data indicators show that this fashion design innovation can be well received by the community, especially in the Pelaihari City area, especially in the aspects of comfort and visual appeal. This positive response indicates a great opportunity to develop traditional fabrics into the realm of modern fashion without losing cultural values, but still paying attention to market segmentation and consumer tastes.